Wits Architecture Student Works 1922-1980; Bryer, Monty (1931, 1933) - Bryer, Monty (My University, 2014)
Design: Sundial , Rest Hut in Natal; Bryer,Monty (architecture student 2nd year 1931 & 4th year 1933; Wits Student Works. University of the Witwatersrand; Johannesburg; South Africa
Design: Sundial , Rest Hut in Natal; Bryer,Monty (architecture student 2nd year 1931 & 4th year 1933; Wits Student Works. University of the Witwatersrand; Johannesburg; South Africa
Keywords: Wits Architecture Student Works 1922-1980; Bryer,Monty 1931, 1933; Sundial - 2nd year, Rest Hut in Natal - 4th year.